Creativity as the axis of intercultural integration: Intensive international mobility programs in higher education - De Prada Creo, Elena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
International mobility has proven to contribute very favourably to university students’ personal, academic and professional development. Ensuring that most students have access to this type of experience should be a priority to guarantee their holistic education. In the case of short-term mobilities, specific planning through creative tourism formulas that allow for optimal use of intercultural exchanges can determine the success of the experience. The evaluation of the proposed model suggests the importance of integrating these types of activities when designing efficient policies.